2008
DOI: 10.1086/591397
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Recent Studies of Community‐Acquired Pneumonia

Abstract: All recent studies of antibacterial drugs for the indication of community-acquired pneumonia submitted to the US Food and Drug Administration have been designed as noninferiority studies. We provide a summary of results of 7 recent clinical studies of oral antibacterial drugs for treatment of community-acquired pneumonia. In these 7 studies, the majority of patients enrolled had Pneumonia Patient Outcomes Research Team scores of I or II. The percentage of randomized subjects with pathogens identified at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Although the studies enrolled patients aged 165 years, the mean age tended to be between 40 and 50 years. S. pneumoniae was identified as the etiological agent in only a fraction of cases, and mortality rates in these studies were very low [31].…”
Section: Conclusion and Limitations Of These Datamentioning
confidence: 84%
See 1 more Smart Citation
“…Although the studies enrolled patients aged 165 years, the mean age tended to be between 40 and 50 years. S. pneumoniae was identified as the etiological agent in only a fraction of cases, and mortality rates in these studies were very low [31].…”
Section: Conclusion and Limitations Of These Datamentioning
confidence: 84%
“…The overall health of the population, including comorbidities; earlier diagnosis; more readily available access to care; and current practice guideline recommendations for early treatment all substantially contribute to the likelihood that patients enrolled in any of the studies described above would not be comparable to patients enrolled in a contemporary CAP trial, even if controlled for age. Higgins et al [31] have summarized data from recent CAP registrational trials. Most of these studies were conducted in outpatients and evaluated oral antibacterial therapy.…”
Section: Conclusion and Limitations Of These Datamentioning
confidence: 99%
“…Then, a minimum of 150 per arm and a maximum of 400 per arm were imposed to avoid simulating unrealistic samples sizes relative to those typically seen in the motivating setting. This choice of range is approximately based upon a study by Higgins et al (2008), in which authors reviewed all comparative studies that were submitted to the Office of Antimicrobial Products to support indications for CAP in the 8 years prior to 2008. They found that among the 7 studies submitted, sample sizes ranged in from about 300 to 500 subjects for oral antibiotics and from about 300 to 700 for intravenous antibacterial drugs.…”
Section: Methods: Simulation Studiesmentioning
confidence: 99%
“…Demonstrating clinical utility of a ketolide agent in precisely the patient population most likely to benefit from this intervention remains a development challenge. The applicability and utility of noninferiority trials in determining the efficacy of new treatment regimens for mild to moderate CAP has come under scrutiny by regulatory agencies (16) and academic investigators since the initiation of this program (12). Specifically, the determination of an acceptable noninferiority margin in the absence of a supported treatment effect of the comparator agent has proven problematic.…”
Section: Discussionmentioning
confidence: 99%
“…This method has also been recently debated, as researchers contest the objectivity of investigator-based assessments as well as their potential to introduce intra-and interobserver variability (16). Current discussion regarding appropriate outcome measurements often centers on the use of patient-reported outcome assessments to circumvent these potential biases.…”
Section: Discussionmentioning
confidence: 99%